Accelerated Vaccine Trials during the COVID-19 Pandemic: A Methodological Review (International Journal of Scientific Research in Science and Technology, 2025)
The COVID-19 pandemic catalyzed a paradigm shift in vaccine development, prompting the adoption of innovative clinical trial methodologies to accelerate timelines without compromising scientific integrity. This review critically examines the methodological adaptations employed during the development of COVID-19 vaccines, including overlapping and adaptive trial designs, the use of platform trials, regulatory flexibilities such as Emergency Use Authorizations, and the integration of decentralized and digitally enabled trial models. Ethical considerations, recruitment strategies, and challenges related to equity and public trust are also explored. While these innovations improved efficiency, they also highlighted the need for sustained attention to equity, transparency, and long-term safety monitoring in future vaccine research.